Intergenerational mobility in South Africa: how much has South Africa changed since the early 1990s? - Ressom, Hagos (School of Economics, 2025)
South Africa has been grappling with persistently high rates of poverty, unemployment, and inequality. These unfortunate realities have their roots in the country's colonial and apartheid past, the legacy of which continues to influence the post-apartheid socioeconomic outcomes. This thesis examines changes over time in the relationship between the education and earnings of South African parents and their children once these are adults. The study uses two independent surveys, one collected in the early 1990s and the other in 2017. The timing of the two surveys enables for an examination of changes in mobility during the first 25 years of democracy. The study contributes to the South African literature on inequality by enriching and extending the cross-sectional empirical evidence on trends in educational and earnings inequality to the intergenerational dimension. The study shows that while intergenerational education mobility has increased considerably, earnings persistence has remained high and almost unchanged between the two periods. Intergenerational relative education mobility, as measured by the intergenerational correlation coefficient, decreased from 0.72 in the first period to 0.43 in the second. On the other hand, intergenerational earnings persistence remained high, with the elasticity estimated to be 0.73 in the first period and 0.70 in the second (among currently employed). These results demonstrate that the well-documented cross-sectional trends in educational and earnings inequality in the post-apartheid period are paralleled in the intergenerational dimension. The study further highlights the continued relevance of parental education to earnings, with the effect of parental education on children's earnings shown to be significant and positive in both periods. The contribution of parental education to children's earnings inequality, however, has been small (relative to the contribution of own education) in both periods. The thesis concludes by emphasizing on the contrasting trends in intergenerational education and earnings inequality in the post-apartheid period and recommends that fixing the quality of education could go a long way in addressing the persistently high levels of intergenerational earnings persistence.